The influence of temperature on the sorption and permeability of CO2 in poly(fluoroalkoxyphosphazene) membranes - Ostwal, Mayur; Lau, Joshua M.; Orme, Christopher J.; Stewart, Frederick F.; Way, J. Douglas (Journal of membrane science, 2009)
This paper reports the transport and sorption properties of poly(fluoroalkoxyphosphazene) (PFAP) membranes for carbon dioxide and nitrogen in both pure and mixed gas experiments. The CO2 permeability decreased from 336 to 142 Barrers with an increase in the CO2/N2 ideal separation factor from 12 to 21 as the membrane temperature was decreased from 303 K to 258 K at feed pressure of 2.9 bars. At lower feed pressure (1.5 bars) the CO2 permeability decreased from 327 to 140 Barrers, while the CO2/N2 ideal separation factor increased from 13 to 22 over the same temperature range. CO2 sorption isotherms were measured using the pressure decay equilibrium method. Solubility of CO2 was determined using the sorption isotherms and the diffusion coefficients were calculated from CO2 permeabilities and solubilities. Sorption isotherms were linear at each temperature for the pressure range studied and the enthalpy of sorption was -5.8 kcal/mol. The solubility coefficient values for CO2 increased from 0.95 to 5.43 cm3 CO2(STP)/cm3 polymer.atm whereas the diffusion coefficient decreased from 2.71 X 10-6 to 0.19 X 10-6 cm2/sec as the temperature decreased from 303 K to 258 K.